Pengaruh Gaya Kepemimpinan, Komunikasi Internal, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan(Studi Kasus Pada PT. Gujati 59 Utama Sukoharjo) - Pertiwi, Erica Dian, Drs. Suyatmin Waskito Adi, M.Si (2016)
This research was representing quantitativeresearch with causal approach. The data source in the form of primary data obtained from questioner. The number of respondens as many 50 people taken by purposive sampling. The data analysis was using multiple linear regressions analyze, accuracy model test covering F test, coefficient determinasi R2 analysis, and then hypothesis analysis was using t test. Based on result of data analysis could be conclusion that leadership style, internal communications, motivate and work discipline to employee performance PT. Gujati 59 Utama Sukoharjo, this matter can be showed by each variable p value <0,05. So that hypothesis from H1 until H4 was truth acceptable. The coefficient determinasi R2 result analysis known equal to 51% the leadership style, internal communications, motivate and work discipline was influencing employee performance